Operasionalisasi Ego, Superego, Dan ID Tokoh Rodion Raskolnikov Dalam Novel Kejahatan Dan Hukuman Karya Fyodor Dostoevsky - Yemima Nyimas Polanjaya; Mut Maynah; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of writing this journal is to analyze the psychological subject of Raskolnikov, the main character in Fyodor Dostoevsky's novel Crime and Punishment from the perspective of psychoanalytic theory. This journal outlines an in-depth psychological analysis of the characters and context of Fyodor Dostoyevsky's novel